Scale Adaptation of Innovation-Outsourcing in Companies - Öncü Yanmaz Arpacı; Ferda Esin Gülel (Istanbul Business Research)
In line with the strategic management approach which was developed in the light of changes in production and markets, there is an emphasis in the literature of this field that companies need to be well managed in order to survive, to benefit from strategic management, and to have a sustainable competitive advantage. This study aimed to adapt and apply a scale of innovation and outsourcing. While adapting the scale, in addition to the data from the qualitative research, three different scales were used in the selection. We arranged a questionnaire and created new questions. The questionnaire consists of eight chapters: the characteristics of companies, outsourcing, supplier relations, suppliers’ satisfaction level, innovation process, innovations in the last five years, and outsourcing-innovation. We collected the data from companies in Turkey, which are on the Fortune 500 list. We analyzed the data with SPSS 23 and AMOS 20. As a result of exploratory and confirmatory factor analyses, the outsourcing scale was composed of 3 dimensions and 20 items. While the innovation scale consisted of 12 items in one dimension. The reliability coefficient of the outsourcing scale is 0.912, and the innovation scale is 0.911. The low number of items facilitates its applicability.